N6-methyladenosine RNA modification regulates the transcription of SLC7A11 through KDM6B and GATA3 to modulate ferroptosis - Haisheng Zhang; Cheng Yi; Jianing Li; Yunqing Lu; Haoran Wang; Lijun Tao; Jiawang Zhou; Yonghuang Tan; Jiexin Li; Zhuojia Chen; Gholamreza Asadikaram; Jie Cao; et al. (Journal of Biomedical Science)
Abstract Background Recent studies indicate that N6-methyladenosine (m6A) RNA modification may regulate ferroptosis in cancer cells, while its molecular mechanisms require further investigation. Methods Liquid Chromatography-Tandem Mass Spectrometry (HPLC/MS/MS) was used to detect changes in m6A levels in cells. Transmission electron microscopy and flow cytometry were used to detect mitochondrial reactive oxygen species (ROS). RNA sequencing (RNA-seq) was employed to analyze the factors regulating ferroptosis. Chromatin immunoprecipitation (ChIP) was used to assess the binding of regulatory factors to the SLC7A11 promoter, and a Dual-Luciferase reporter assay measured promoter activity of SLC7A11. The dm6ACRISPR system was utilized for the demethylation of specific transcripts. The Cancer Genome Atlas Program (TCGA) database and immunohistochemistry validated the role of the METTL3/SLC7A11 axis in cancer progression. Results The m6A methyltransferase METTL3 was upregulated during cancer cell ferroptosis and facilitated erastin-induced ferroptosis by enhancing mitochondrial ROS. Mechanistic studies showed that METTL3 negatively regulated the transcription and promoter activity of SLC7A11. Specifically, METTL3 induced H3K27 trimethylation of the SLC7A11 promoter by suppressing the mRNA stability of H3K27 demethylases KDM6B. Furthermore, METTL3 suppressed the expression of GATA3, which regulated SLC7A11 transcription by binding to the putative site at − 597 to − 590 of the SLC7A11 promoter. METTL3 decreased the precursor mRNA stability of GATA3 through m6A/YTHDF2-dependent recruitment of the 3′-5′ exoribonuclease Dis3L2. Targeted demethylation of KDM6B and GATA3 m6A using the dm6ACRISPR system significantly increased the expression of SLC7A11. Moreover, the transcription factor YY1 was responsible for erastin-induced upregulation of METTL3 by binding to its promoter-proximal site. In vivo and clinical data supported the positive roles of the METTL3/SLC7A11 axis in tumor growth and progression. Conclusions METTL3 regulated the transcription of SLC7A11 through GATA3 and KDM6B to modulate ferroptosis in an m6A-dependent manner. This study provides a novel potential strategy and experimental support for the future treatment of cancer.